A Novel Wisdom Network Design and Its Principles - Fuhong Lin; Xianwei Zhou (Institute of Advanced Engineering and Science, 2013)
Next generation network is a hot topic that lots of researchers have paid their attention to this point. The main idea is making people more comfortable and convenient. This paper presents a novel wisdom network which tends to achieve the above mentioned advantages. This network is composed by User Part and Server Part. Further, Server Part is divided into Gateway Server part and Data Server part. According to the network architecture, some design principles are analyzed and modeled, including the following aspects: resource registration and retrieval, data pieces replication, Gateway Server performance and load balance achievement. Key word:Wisdom network, resource registration and retrieval, data replication, load balance. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3584